Evaluasi Penerapan Aspek 5M Dalam Penggunaan Tracer di Unit Penyimpanan Rekam Medis RSIA Husada Bunda Malang - Nor Mauizzatun Indah F; Eiska Rohmania Zein (Jurnal Rekam Medis dan Informasi Kesehatan, 2023)
Tracer is an outguide when medical record documents are borrowed or taken by health workers in health services. Tracers at RSIA Husada Bunda is still not appropriate, seen in terms of the design of the marker slip which does not include the destination poly and the use of tracers is still done manually. This study aims to evaluate the use of tracers based on 5M aspects in the medical record unit of RSIA Husada Bunda. This research was conducted using a descriptive qualitative method with instruments in the form of observations and interviews conducted to the head of medical records and medical records officers in the storage section. The results of this study show that in the Man aspect there are discrepancies related to HR criteria in the medical records unit. In the Material aspect, the tracer uses semihard materials, while the use of the tracer refers to a special method, namely the SOP. The application of the tracer in terms of Machine still uses a written manual. In supporting all activities in the medical records unit, it is supported by Money (budget funds) and some are allocated for training activities and seminars. Overall, the use of tracers in the medical records unit of RSIA Husada Bunda has been relatively effective but still needs a stage of improvement in several aspects. Improvements related to the use of tracers can be in the form of updates to tracer materials, redesign of marker slips, and maximizing the use of machines in operational activities using tracers.